Characterization of a small cryptic plasmid from endophytic Pantoea agglomerans and its use in the construction of an expression vector - Procópio Rudi Emerson de Lima; Welington Luiz Araújo; Fernando Dini Andreote; João Lúcio Azevedo (Genetics and Molecular Biology, 2011)
A circular cryptic plasmid named pPAGA (2,734 bp) was isolated from Pantoea agglomerans strain EGE6 (an endophytic bacterial isolate from eucalyptus). Sequence analysis revealed that the plasmid has a G+C content of 51% and contains four potential ORFs, 238(A), 250(B), 131(C), and 129(D) amino acids in length without homology to known proteins. The shuttle vector pLGM1 was constructed by combining the pPAGA plasmid with pGFPmut3.0 (which harbors a gene encoding green fluorescent protein, GFP), and the resulting construct was used to over-express GFP in E. coli and P. agglomerans cells. GFP production was used to monitor the colonization of strain EGE6gfp in various plant tissues by fluorescence microscopy. Analysis of EGE6gfp colonization showed that 14 days after inoculation, the strain occupied the inner tissue of Eucalyptus grandis roots, preferentially colonizing the xylem vessels of the host plants.